TEMA DAN AMANAT KUMPULAN CERPEN SERIMPI DAN KELAYAKANNYA DALAM PEMBELAJARAN DI SMA - Fikri Ariyanto; Kahfie Nazaruddin; Edi Suyanto (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2014)
The research problem is how the theme and the moral message of the short story "Larasati", "DJ", “Sepenggal Aku”, "Serimpi" on a collection of short stories Serimpi by Rohana Handaningrum and its feasibility work in the learning literature in high school. This purpose of this study is to describe the theme and the moral message of the short story "Larasati", "DJ", “Sepenggal Aku”, and "Serimpi". The method used is descriptive. Sources of research data is the short story "Larasati", "DJ",“Sepenggal Aku”, and "Serimpi". Techniques of collecting and analyzing research data is text analysis techniques. The results of the study is the woman figures spirit on ideas and ideals and take heart and dare to realize the mandate of every faith. Short Story "Larasati", "DJ", “Sepenggal Aku”, "Serimpi" on a collection of short stories Serimpi by Rohana Handaningrum are feasible as teaching materials in high school.Masalah penelitian ini adalah bagaimana tema dan amanat cerpen “Larasati”, “DJ”, “Sepenggal Aku”, “Serimpi” pada kumpulan cerpen Serimpi karya Rohana Handaningrum dan kelayakannya dalam pembelajaran sastra di SMA. Penelitian ini bertujuan mendeskripsikan tema dan amanat cerpen “Larasati”, “DJ”, “Sepenggal Aku”, dan “Serimpi”. Metode penelitian yang digunakan adalah deskriptif. Sumber data penelitian adalah cerpen “Larasati”, “DJ”, “Sepenggal Aku”, dan “Serimpi”.Teknik pengumpulan dan analisis data penelitian adalah teknik analisis teks. Hasil penelitian ini adalah tema semangat hidup tokoh-tokoh perempuan atas gagasan dan cita-citanya dan amanat bersemangatlah dan berani mewujudkan setiap keyakinan. Cerpen “Larasati”, “DJ”, “Sepenggal Aku”, “Serimpi” pada kumpulan cerpen Serimpi karya Rohana Handaningrum layak sebagai bahan ajar sastra di SMA.Kata kunci: amanat, cerita pendek, tema.